2017
DOI: 10.1248/bpb.b17-00313
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Danshensu-Tetramethylpyrazine Conjugate DT-010 Provides Cardioprotection through the PGC-1α/Nrf2/HO-1 Pathway

Abstract: In this study, we investigated the cardioprotective mechanisms of action of DT-010, a novel danshensutetramethylpyrazine conjugate. DT-010 significantly preserved cell viability and suppressed cell apoptosis in H9c2 cells injured by tert-butylhydroperoxide (t-BHP), iodoacetic acid (IAA) and hypoxia-reoxygenation. In addition, DT-010 pre-treatment reduced the intracellular level of free radicals including superoxide anion (·O 2 ), hydroxyl radical (·OH) and peroxynitrite anion (ONOO ) after t-BHP exposure. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…Thus, a series of novel derivatives of Danshensu have been developed. Pharmacological investigations have shown that these derivatives prevent myocardial ischemia injury in the heart, confirming their therapeutic potential in heart diseases [256][257][258][259][260][261] . Additionally, the combination of Danshensu and other agents, such as hydroxysafflor yellow A [262] , paeonol [263,264] , and puerarin [265,266] , shows synergistic cardioprotective effects, thus providing additional options for the clinical uses of Danshensu.…”
Section: Cardioprotective Effects Of Danshensu Derivatives and Preparmentioning
confidence: 66%
“…Thus, a series of novel derivatives of Danshensu have been developed. Pharmacological investigations have shown that these derivatives prevent myocardial ischemia injury in the heart, confirming their therapeutic potential in heart diseases [256][257][258][259][260][261] . Additionally, the combination of Danshensu and other agents, such as hydroxysafflor yellow A [262] , paeonol [263,264] , and puerarin [265,266] , shows synergistic cardioprotective effects, thus providing additional options for the clinical uses of Danshensu.…”
Section: Cardioprotective Effects Of Danshensu Derivatives and Preparmentioning
confidence: 66%
“…More recently, we have demonstrated that DT-010 was able to enhance the chemotherapeutic efficacy of doxorubicin in tumor cells ( Wang et al, 2016 ). Additionally, DT-010 could offer cardioprotection and neuroprotection against Parkinson’s disease-related neurotoxins ( Hu et al, 2016 ; Zhang et al, 2017 ). However, the neuroprotective effects of DT-010 in cellular models associated with AD have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Research finds that the Nrf2-ARE signaling pathway is closely related to improving myocardial I/R injury. Meanwhile, Nrf2 is an important transcription factor in cell to reduce ROS (22). Our results suggest that the effects of hyperoxia liquid induced Nrf2-ARE signaling pathway in CPB induced rat model.…”
Section: Discussionmentioning
confidence: 56%